EVOLUTION OF ISLAMIC LAW AND ITS INTERPRETATION - Dr. Meena Kumari (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The paper deals with the origin of Islamic law, its sources, how it develops in its present form, and the further scope of reform and interpretation. The paper deals with this issue of interpretations because we have seen a lot of controversy on the law of talaq. It is necessary to understand the nature and development of Islamic law to find out the root cause of the problem. On one hand, the traditionalists were of the view that there should be no reformation and codification of the Islamic law in India as it was based on the Sharia, the divine law, but on the other hand, sweeping reforms and codification were introduced mostly by Muslim countries around the world. Thus, the purpose of this paper was to point out that Islamic law in spirit is not in contravention of reform as it has evolved from its origin till the date by way of different interpretations according to the needs of society.